Pengembangan Minyak Daun Cengkeh dan Stevia sebagai Sabun Padat Antibakteri terhadap Escherichia coli - Alif Alfakhur Ridla; Kun Harismah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Indonesian clove product mostly has been used as main component of kretek ciggarete, which is undermining outcome because of health issue. Diversification of clove product should be considered in order to maintain the clove’s price. On the other hand clove can be used as soap product due to particular asset inside clove leaf that contain eugenol which has resistance behavior toward bacterial pathogen. Triclosan also becomes problem on major soap product due to allergy on skin, stevioside compound from steavia leave that has antibacterial behavior, similar with clove leaf oil can resolve this issue. These components have immersive benefit synergy as soap product. It become concern of the research to determine the appropriate composition. Soap production process has 3 various formulation which are expected bringing upcoming result toward indonesian national standard known as SNI. The quality assurance including pH degree value, water content analysis, and microbiology susceptibility test. The optimal result of this research is formula F2 with pH 8.64, water content 4.6 % and microbiology susceptibility test is 21.67 mm